2015
DOI: 10.18287/jbpe-2015-1-2-135
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic crystallogram images classification

Abstract: Abstract.A computer classification system of dendritic crystallogram images is presented in this paper. To improve the quality of classification we use an algorithm for the informative features formation, using methods of discriminant analysis. The method for receiving an informativeness estimation was used. As basic features are seven geometric characteristic was calculated. The research confirming the efficiency of the formed features for classification of dendritic crystallogramms images was conducted by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The method of crystallogram analysis was used for adequate assessment of structural changes occurring under action of laser radiation in biosimilar liquids as one of the simplest methods of structural changes diagnostics. Crystallograms of biological fluids were formed due to dehydration self-organization of protein solutions and other substances [6,11] during drying of solution droplets on a solid substrate. It was found that the resulting patterns correlate well with the signs of J of Biomedical Photonics & Eng 5 213 May 2019 © J-BPE 020301-2 patients' diseases [6,12,13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of crystallogram analysis was used for adequate assessment of structural changes occurring under action of laser radiation in biosimilar liquids as one of the simplest methods of structural changes diagnostics. Crystallograms of biological fluids were formed due to dehydration self-organization of protein solutions and other substances [6,11] during drying of solution droplets on a solid substrate. It was found that the resulting patterns correlate well with the signs of J of Biomedical Photonics & Eng 5 213 May 2019 © J-BPE 020301-2 patients' diseases [6,12,13].…”
Section: Methodsmentioning
confidence: 99%
“…But ways of detecting changes that occur under action of laser radiation recently have significantly expanded. Thus, different experimental techniques of structural changes of complex organic solutions such as Raman spectroscopy and IR spectroscopy, crystallographic method and method of speckle patterns processing have become widespread in practice [2][3][4][5][6][7][8]. Using new research methods has led to appearance of some new theories about the mechanisms of action of laser radiation on living organisms [1,4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [6][7][8][9][10] it is shown that in relation to the protein and bile solutions this statement finds its experimental confirmation.…”
Section: Introductionmentioning
confidence: 93%
“…One of the simplest and clear methods for monitoring the structure modifications in liquid media is crystallography, in which the segment size of a crystallogram is directly related to the characteristic size of inhomogeneities in biological liquids [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of dehydration self-organisation is chosen to be the basis of one of the medical diagnostic methods, the method of wedge-shaped dehydration [8][9][10] that consists in the following. A droplet of the studied biological liquid (for the control samples and the ones exposed to laser radiation) with the volume 0.01 ml is deposited on the defatted object glass and dried tilted at the angle 25-30º and dust-protected at room temperature 20-25ºС and relative air humidity 65-70% during 18-24 hours.…”
Section: Introductionmentioning
confidence: 99%